A Market Share Model for FMCG - Shepard, Deborah (My University, 2011)
Marketing, as a discipline, is becoming increasingly business orientated with a focus on internal profitability, growth and revenue projection being closely linked to marketing activities and their impact on market share. Despite the utilisation of market share as a key measure for performance, very little understanding exists on how marketing levers impact market share, and the relative strength of the impact. It is in this environment that the researcher seeks to develop a prediction tool in the form of a market share model for FMCG brands in South Africa. In order to develop a model, consumer choice behaviour was explored, the key marketing activities focusing on McCarthy’s (1993) 4P’s were identified that impact market share, and a Conceptual Market Share Model was developed that integrated the plethora of literature into a visual representation of the relationships and inter-relationships between the numerous marketing mix variables. While a total of twenty-one variables were identified as having an impact on market share, the key levers were identified as advertising intensity, brand equity, penetration and distribution, consumption, loyal customers, structural price change, price promotion, depth of promotion and stockpiling. A review of the commonly available quantitative data in South Africa which included Nielsens Nitro, Nielsens Homepanel and Adex, determined that the majority of key identified variables were available with the exception of sales promotion activities, namely price promotion, depth of promotion and stockpiling. An MCI Model was utilised for the purposes of developing a market share model with quantitative single-intersect data from three independent FMCG categories’ being used in order to compare results across categories. A number of permutations of the model were done for each category with an ii i Adjusted MCI Model being developed that incorporated growth indicators as moderators to specific variables. As a managerial tool, some questions were raised regarding the reliability of the MCI Model due to high variances between brands’ actual market share and estimated share, as well as the negligible impact advertising spend was found to have on market share which is contrary to the body of literature. However, the model did provide insights into the key levers that impact market share and how each category has unique category drivers that are specific to that market environment and competitive set. As such, their was a partial acceptance of the proposition in terms of the proposed marketing mix variables and the development of a market share model for FMCG brands in South Africa.
MBA - WBS
Keywords: Marketing; Branding